Carbon‐Shielded Selenium‐Rich Trimetallic Selenides as Advanced Electrode Material for Durable Li‐Ion Batteries and Supercapacitors. Issue 3 (15th January 2023) - Kakarla, Ashok Kumar; Bandi, Hari; Shanthappa, R.; Yu, Jae Su
Abstract: In order to achieve a sustainable future, researchers must continue to research improved electrode materials. Considering the high electronic conductivity, versatile redox activity, and enhanced energy storage performance, nanostructures have been employed as a novel electrode material for high‐performance lithium‐ion batteries (LIBs) and supercapacitors. Herein, carbon‐coated selenium‐rich trimetallic selenide (Cu2 NiSnSe4 @C) nanoparticles (NPs) as an efficient electrode material in energy storage devices are prepared. The prepared core‐shell Cu2 NiSnSe4 @C NPs electrode is employed as an anode material for LIBs, which demonstrated a high reversible specific capacity of 988.46 mA h g −1 over 100 cycles at 0.1 A g −1 with good rate capability. Additionally, the core‐shell Cu2 NiSnSe4 @C NPs electrode exhibited an outstanding capacity of 202.5 mA h g −1 at 5 A g −1 even after 10 000 cycles. Exploiting the synergistic characteristics, the core‐shell Cu2 NiSnSe4 @C NPs material is also investigated as a battery‐type electrode for hybrid supercapacitors. The assembled hybrid supercapacitor with Cu2 NiSnSe4 @C NPs and activated carbon showed excellent rate capability including high power (5597.77 W kg −1 ) and energy (64.26 Wh kg −1 ) densities. Considering the simple synthesis and enhanced energy storage properties, carbon‐coated selenium‐rich trimetallic selenide can be used as a durable electrode material for practical energy storage devices. Abstract : The core‐shell Cu2 NiSnSe4 @C nanoparticles (NPs) are synthesized and used as an electrode material for Li‐ion batteries (LIBs) and hybrid supercapacitors. In LIBs, it exhibits high reversible cycling capacity with good rate capability. The core‐shell Cu2 NiSnSe4 @C NPs are also employed as a battery‐type electrode for a hybrid supercapacitor. The fabricated hybrid supercapacitor shows excellent energy and power densities.